A trial of Criminal Infringement Notices as an alternative to criminal penalties for illicit drug offences in New South Wales, Australia: Estimated savings. (14th September 2020) - Sutherland, Rachel; Weatherburn, Don; Degenhardt, Louisa
Abstract: Introduction and Aims: In 2019, legislation was introduced allowing New South Wales police to issue Criminal Infringement Notices (CIN) instead of criminal charges for prohibited drug possession offences, excluding cannabis leaf. This initiative was trialled across NSW music festivals from 25 January to 1 August 2019. This paper aims to examine the number of CINs administered and to estimate the associated (actual and potential) savings. Design and Methods: Data were obtained from the NSW Bureau of Crime Statistics and Research (Recorded Crime Statistics, Reoffending Database). To estimate the monetary savings associated with administering CINs for drug possession offences, as opposed to processing them through the criminal justice system, data were obtained from the 2020 Report on Government Services . Results: From January to June 2019, 300 CINs were issued for illicit drug possession (mostly for ecstasy possession; n = 256), resulting in an estimated saving to the criminal justice system of 194 400 AUD (or 314 400, if generated revenue included). We estimate that issuing CINs for all illicit drug possession offences would have provided savings of over 5 million AUD in that same six‐month period, or approximately 1.7 million AUD if CINs were only issued to people with no prior convictions. Discussion and Conclusion: Issuing CINs for illicit drug possession has the potential to yield substantial monetary savings. However, to avoid unintended consequences (e.g. disproportionate impact on disadvantaged populations), we would argue that police also be given the discretion to issue cautions for illicit drug possession offences.